Comprehensive Review of Surgical Techniques for Correcting Cephalic Malposition of the Lower Lateral Cartilages in Rhinoplasty - Aref Nassar, MD, MBE; Joy Naba, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Lateral crural malposition, characterized by lower lateral cartilages diverging less than 30 degrees from the midline toward the ipsilateral medial canthus, presents both functional and aesthetic challenges in rhinoplasty. Various surgical techniques have been described for correction, but no comprehensive review has compared their efficacy. Methods:. A literature review was conducted to categorize and evaluate surgical techniques for correcting cephalic malposition. Techniques were grouped into flaps, grafts, lateral crura transection, and suture-based methods. Functional and aesthetic outcomes, as well as factors influencing technique selection, were analyzed. Results:. The selection of a surgical technique depends on factors such as surgeon expertise, cartilage availability, and patient-specific anatomical considerations. Although multiple techniques have demonstrated favorable outcomes, long-term data on complications and structural stability remain limited, highlighting the need for further research. Conclusions:. This article is the first to comprehensively describe and compare surgical techniques for cephalic malposition correction. Further research is needed to establish evidence-based guidelines for technique selection and to assess long-term functional and aesthetic outcomes.